Lighting quality evaluation on growth performance and feather pecking behavior of broilers - Chenghao Pan; Rong Xiang; Jinming Pan (Poultry Science)
Light is an important factor affecting the feather pecking behavior in poultry. To evaluate the quality of lighting in production of a local broiler breed, this study was designed to investigate the effects of light color on the growth performance (body weight, feed conversion ratio and upper beak length), welfare parameters (walking step, plumage damage and hormone level) relating to feather pecking and their correlations. One hundred and twenty 49-day-old Youhuang broilers were randomly distributed into 3 lighting treatment groups (warm white, cold white and red) and reared for 4 weeks. The results showed that the lighting had no significant effect on the growth performance (P > 0.05). The daily walking steps of birds in cold white group were greater than birds in warm white and red group at 8 (P < 0.05) rather than 9 to 11 (P > 0.05) weeks of age. Compared with birds in red group, the birds in cold white group had lower plumage scores (P < 0.05) and the birds in warm white group had similar plumage scores (P > 0.05). Lower scores meant severer plumage damage. Moreover, the plumage scores of backs and wings were both lower than those on tails (P < 0.05). The serotonin levels in blood of birds in warm white group were greater than those in cold white group (P < 0.05) but lower than those in red group (P < 0.05). However, during the entire study, there were no correlations among body weight gain ratios, upper beak length gain ratios, average daily walking steps, total plumage scores of different body parts, and serotonin levels of 24 selected birds in three light treatment groups (P > 0.05). Considering the friendliness of white light to human eye, warm white light should be recommended to reduce pecking behavior in production.